PENGEMBANGAN MEDIA CERITA BERGAMBAR PADA MATERI DONGENG SISWA KELAS II SEKOLAH DASAR - Nurul Hidayani; Liza Murniviyanti (STKIP Subang, 2023)
This research was conducted at SD Negeri 6 Muara Telang, Banyuasin district, to find out the Development of Pictorial Story Media on Fairy Tales for Grade II Elementary School Students in Grade II students. The problem in this research is that the media used is still not attractive and innovative. The purpose of this study was to describe the validity and practicality of the results of the development of Pictorial Story Media on Fairytale Material for Grade II Elementary School Students. This type of research includes development research. The method used is the development research method or called Research and Development, and uses the ADDIE development model. The results of the development of picture story media at SD Negeri 6 Muara Telang, Banyuasin district. Based on the results of the data analysis which was distributed to the three experts, the score of linguists was 95% in the very practical category, media experts 96% in the very practical category and material experts 100% in the very practical category, meaning that the media can be concluded that the validity of the results of developing picture story media in material Fairy Tales for class II Elementary School students are very valid, and based on the results of the questionnaire distributed to students, a score of 76% is obtained, it can be concluded that practical and practical value criteria based on table 6, it can be concluded that Picture Story media is practical for use by the teacher as one of the media in the teaching and learning process in dogeng material at II SD Negeri 6 Muara Telang.